Factors associated with treatment success among pulmonary tuberculosis and HIV co-infected patients in Oyo State, South West-Nigeria (2013)
BACKGROUND The co-existence of Tuberculosis (TB) and Human immunodeficiency Virus (HIV) is known to increase morbidity and mortality in patients. The determinants of treatment success in TB- HIV co-infection are not yet well studied. Such information can help optimise treatment and reduce morbidity and mortality. OBJECTIVE To determine factors associated with anti- tubercular treatment success among TB /HIV coinfected patients. METHODS A cross sectional study was carried out in fifty three DOT clinics and treatment centres using tuberculosis patient’s records from January 2009 to December 2010 in Oyo state, Nigeria. The study population consisted of 7905 tuberculosis patients. Information on variables of interest were obtained with the use of data extraction forms. Chi-square and logistic regression were used to test the relationship between TB/ HIV co- infection and socio-demographic variables, clinical characteristics and treatment success. RESULTS Prevalence of TB /HIV co-infection was found to be 14.2%. Patients with TB-HIV co-infection were younger and more likely to be females. There were statistically significant association between treatment success and gender, marital status and patient point of care. After adjusting for other variables, it was found that patients receiving treatment in private facilities were independently less likely to be successfully treated compared with those receiving care in Public facilities. Female patients were also independently more likely to have better treatment outcome than male. CONCLUSION In addition to patients’ point of care, gender of the patients can adversely impact on their treatment success. Efforts from the government to strengthening the private public mix, health education and media awareness on adherence to treatment to improve treatment success should be intensified in the country.